Current treatment strategies in pediatric alopecia areata - Etienne Wang; Joyce SS Lee; Mark Tang (Wolters Kluwer Medknow Publications, 2012)
Alopecia areata (AA) is a non-scarring autoimmune disease of the hair follicle that can present at any age. Pediatric cases are commonly seen in a dermatology clinic, and management can potentially be challenging, with a small proportion of cases experiencing a chronic relapsing course marked by distressing hair loss that can bring about significant psychosocial morbidity. We review the established treatments for pediatric alopecia areata, alongside second and third line therapies that have shown to be efficacious. We also offer a treatment algorithm as a guide to the treatment of pediatric AA.